2009
DOI: 10.1590/s0004-282x2009000600022
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of stroke risk factors and warning signs in southern Brazil

Abstract: -Objective: To evaluate the knowledge about stroke in Caxias do Sul. Method: A closed-ended, self-administered questionnaire was used to assess the knowledge about stroke among residents of Caxias do Sul. In order to verify variables associated to lack of knowledge we defined three main end points: (1) the inability to recognize that stroke is a disease that affects the brain; (2) insufficient knowledge of risk factors; (3) insufficient knowledge of signs and symptoms of acute stroke. Results: A total of 952 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
3
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 19 publications
(23 reference statements)
5
23
3
9
Order By: Relevance
“…It has been reported that people with low levels of education and income have less knowledge about stroke, even among those who have experienced a previous event or who have had a family historyof stroke 34,35 . Previous studies performed in Brazil reinforce our findings about the relationship between socioeconomic and functional outcome 36,37 . Moreover, low levels of education may interfere with treatment adherence and medical recommendations.…”
Section: Risk Factors (Variables)supporting
confidence: 90%
“…It has been reported that people with low levels of education and income have less knowledge about stroke, even among those who have experienced a previous event or who have had a family historyof stroke 34,35 . Previous studies performed in Brazil reinforce our findings about the relationship between socioeconomic and functional outcome 36,37 . Moreover, low levels of education may interfere with treatment adherence and medical recommendations.…”
Section: Risk Factors (Variables)supporting
confidence: 90%
“…However patients aware of stroke therapeutic time window had a trend towards a higher household income. Most studies from developed and underdeveloped countries have found that knowledge about stroke varies positively with income and education 6,7,15,16 . The lack of association between household income and stroke symptoms awareness in our patients might be explained by the homogeneously low educational level and socioeconomic status of the population we evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A previous community-based study has shown alarming lack of awareness about stroke in Brazil. Most of the studies evaluating knowledge about stroke symptoms in the country have been conducted in the general population 6,7,8 . Little is known about stroke patients' awareness about stroke warning signs and its therapeutic time window and how these factors influence the timing of seeking for medical care in Brazil.…”
mentioning
confidence: 99%
“…Mansur (2011) indicated that the percentage of individuals that could identify at least one sign/symptom of stroke varied from 25% to 79.9%. Other studies show that knowledge about initial signs and symptoms of stroke amongst the general populations is low (FALAVIGNA et al, 2009;SILVA et al, 2012;OBEMBE et al, 2014;PONTES NETO, 2014). Moreover, individuals with the least severe cases, and therefore those with better prognosis, tend to delay in seeking medical care, losing the therapeutic window which is paramount for a positive outcome in the natural evolution of the disease (COSTA et al, 2008).…”
Section: Discussionmentioning
confidence: 99%